STRATEGI PERTUMBUHAN WISATA BUDAYA DAN RELIGI MELALUI PROMOSI DIGITAL, KEARIFAN LOKAL DAN KEMITRAAN DI KOTA CIREBON - Micki Watulandi; Januar Habibi Mahsyar; Qona’ah El Hasan; Achmad Sahroni (Jurnal Perilaku dan Strategi Bisnis, 2025)
Cultural and religious tourism holds significant potential in driving economic growth while preserving cultural heritage. This study examines strategies for developing cultural and religious tourism in Cirebon City through digital promotion, partnerships, and local wisdom. Field surveys conducted at Keraton Kesepuhan, Keraton Kacirebonan, Gua Sunyaragi, and the Tomb of Sunan Gunung Jati revealed a lack of collaboration among destinations, manual ticketing systems, and limited access to tourism information. This research employed a qualitative approach through literature review, documentation, observation, and interviews with relevant stakeholders. Secondary data were obtained from previous studies and tourism regulations. The findings highlight that digital promotion is effective in enhancing destination exposure; however, its utilization in Cirebon remains limited. Partnerships among stakeholders have not been fully optimized, making the creation of integrated tourism packages challenging. Meanwhile, local wisdom in the form of traditions, cultural values, and religious identity shows strong potential as a distinctive attraction but has not been systematically integrated into management strategies. The study concludes that the growth of cultural and religious tourism in Cirebon requires synergy among digital promotion, cross-sector partnerships, and the utilization of local wisdom. Integrating these three aspects is essential to strengthen tourism competitiveness while improving community welfare.